The Dialectic of Ideas About Urban Restoration in Indonesia: The Political Communication of Presidential Candidates at the APEKSI Forum in Makassar - Ropingi el Ishaq; Prima Ayu Rizqi Mahanani (Mediakita, 2025)
The dialectic of ideas presented by the presidential candidates becomes important for people when deciding whom to vote for. This research aims to examine the ideas presented by the presidential candidates during the forum related to urban restoration. The analysis of the study employs critical discourse analysis, incorporating observation and documentation methods. The results of the study show that Ganjar Pranowo presented ideas related to the programs he run in the provincial government. He primarily discussed the importance of accountability and transparency as a manifestation of his election promise. He did not discuss the city dynamics. He briefly discussed the importance of local governments actively utilizing the global market. His political background and experiences did not provide support for formulating the concept of urban restoration. On the other hand, Anies Rasyid Baswedan systematically explained the problems, challenges, and principles of an ideal city that must be considered and implemented by the local governments. The problems of urbanization, fiscal capacity, social disparities in urban communities, environmental conditions, and the roadmap that needed to be carried out by the mayors and their staff were presented coherently. His bright ideas on the city cannot be separated from his insight and experiences. He was once the Rector of Paramadina University. He also achieved many notable accomplishments during his tenure as Governor of DKI Jakarta. Meanwhile, Prabowo Subianto did not mention about city problems. Prabowo emphasized that the downstream program, which will become the state government’s initiative, will later be financially beneficial for the mayors.